Brain Correlates of Mental Stress-Induced Myocardial Ischemia. Issue 6 (July 2018) - Bremner, J. Douglas; Campanella, Carolina; Khan, Zehra; Shah, Majid; Hammadah, Muhammad; Wilmot, Kobina; Al Mheid, Ibhar; Lima, Bruno B.; Garcia, Ernest V.; Nye, Jonathon; Ward, Laura; Kutner, Michael H.; et al.
ABSTRACT: Objective: Coronary artery disease (CAD) is a major cause of morbidity and mortality, and despite important advances in our understanding of this disorder, the underlying mechanisms remain under investigation. Recently, increased attention has been placed on the role of behavioral factors such as emotional stress on CAD risk. Brain areas involved in memory and the stress response, including medial prefrontal cortex, insula, and parietal cortex, also have outputs to the peripheral cardiovascular system. The purpose of this study was to assess the effects of mental stress on brain and cardiac function in patients with CAD. Methods: CAD patients ( N = 170) underwent cardiac imaging with [Tc-99m] sestamibi single-photon emission tomography at rest and during a public speaking mental stress task. On another day, they underwent imaging of the brain with [O-15] water positron emission tomography (PET) during mental stress (arithmetic and public speaking) and control conditions. Results: Patients with mental stress–induced myocardial ischemia showed increased activation with stress in anterior cingulate, inferior frontal gyrus, and parietal cortex ( p < .005). This was seen with both arithmetic stress and public speaking stress. Arithmetic stress was additionally associated with left insula activation, and public speaking with right pre/postcentral gyrus and middle temporal gyrus activation ( p < .005). Conclusions: These findings suggest that mental stress–induced myocardial ischemia is associated with activation in brain areas involved in the stress response and autonomic regulation of the cardiovascular system. Altered brain reactivity to stress could possibly represent a mechanism through which stress leads to increased risk of CAD-related morbidity and mortality.